As trilhas possíveis da inclusão de pessoas com deficiência na educação profissional do IFES Vitória: narrativas dos protagonistas - Mendes, Joselma de Vasconcelos (2013)
This research aims to understand how it develops the inclusion of people with disabilities in the Technical Course in Occupational Safety Ifes Victory in the perspective of the individuals involved in the process. It is an investigation of qualitative / interpretive - a case study - begun in June 2012, performed with two physically handicapped students, two teachers and four current managers, educators and education director. Visa enable moments of listening to the subjects and your own knowledge, identify paths taken by the institution to carry out the work with disabled people (laws, educational projects, teaching plans) and analyze possibilities for transformative action in the context of inclusive education, considering the sociohistorical context of the institution Ifes. Fundamenta his gaze, which seeks qualified listening in mind grasp the uniqueness of each one in Freire and Benjamin. It uses narrative and semi-structured interviews, which are organized in the form of interviews, narratives, in which the lines of each segment - students, teachers and administrators - is grouped into three themes: the beginning of the process in the perception of each individual participant the inclusion process in progress, with its possibilities, tensions and challenges, and achievements and wishes. The subjects are narrated and the inclusion process experienced since its inception - with entry into the institution - outlining the important facts, possibilities, tensions, challenges and desires and achievements. This indicates some listening tracks for which inclusion can be made possible, trails that pass by the appreciation of the experience, listening as professional duty and ethical dialogue in which no judgment and stigmatization of the other possibilities, intentionality in collective struggle, and drawing outputs to emancipatory education of the subjects themselves, a process of listening and socio- historical, cultural and political, who believes in "untested feasibility" as a real possibility